Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1155/2011/537824
|View full text |Cite
|
Sign up to set email alerts
|

Impeller Design of a Centrifugal Fan with Blade Optimization

Abstract: A method is presented for redesigning a centrifugal impeller and its inlet duct. The double-discharge volute casing is a structural constraint and is maintained for its shape. The redesign effort was geared towards meeting the design volute exit pressure while reducing the power required to operate the fan. Given the high performance of the baseline impeller, the redesign adopted a high-fidelity CFD-based computational approach capable of accounting for all aerodynamic losses. The present effort utilized a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…This technique therefore enables the optimisation of complex geometries (Sun et al, 2010). It has also been widely used in different optimisation problems (Lee et al, 2011;Li et al, 2016;Sun et al, 2010).…”
Section: Geometry Regenerationmentioning
confidence: 99%
“…This technique therefore enables the optimisation of complex geometries (Sun et al, 2010). It has also been widely used in different optimisation problems (Lee et al, 2011;Li et al, 2016;Sun et al, 2010).…”
Section: Geometry Regenerationmentioning
confidence: 99%
“…A typical example (among many others) is the work by Lee et al [7] who used CFD-based optimization to reduce the shaft power of a centrifugal fan by 9 %. While CFD-based optimization can yield a highly efficient design of a specific machine, it suffers from long computing times.…”
Section: Figure 1: Examples Of Centrifugal Fan Impellers For Differenmentioning
confidence: 99%
“…They reported that increase in the number of blade increases the flow coefficient and efficiency. Lee and coworkers in 2011 [Lee et al 2011] presented numerical CFD optimization with experiential steering technique to redesign the backward centrifugal fan profile, inlet duct and shroud of the impeller. The goal of optimization was to reduce power consumption while maintaining a specified output pressure at the lift-side volute exit.…”
Section: Introductionmentioning
confidence: 99%